Development of a Self-Control-Based Psychoeducation Website to Reduce Online Game Addiction in Vocational School Students: english - Mahdia, Farha; Yanuari Srianturi,; Nabila Fuadina, (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
The development of online games in adolescents has an impact on decreased study concentration, late assignments, and low time management due to weak self-control, as found in SMK Negeri 4 Bojonegoro students. This research aims to develop and determine the feasibility of self-control-based psychoeducation website media as a means of guidance and counseling services in helping to reduce online game addiction. The research uses the Research and Development (R&D) method with the ADDIE model. Data were collected through a Likert scale questionnaire and analyzed using the Percentage Agreement (PA) technique. The results of the study showed that the media had a very good level of eligibility, with the validation of guidance and counseling experts of 90.22%, learning experts 88.57%, and BK teachers of 88.88%. User tests also show excellent results with an average of 86.01%, which shows the medium is decent, attractive, and easy to use. The novelty of this research lies in the self-control approach in the psychoeducational website with interactive features. However, this study is limited to a feasibility test and has not tested its effectiveness and long-term impact. Therefore, further research is recommended to test the effectiveness of the media and develop more adaptive features.